2017
DOI: 10.13075/ijomeh.1896.01037
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous administration of infliximab-attenuated silica-induced lung fibrosis

Abstract: Objectives: To investigate the influence of the anti-tumor necrosis factor-α infliximab (IFX) in the case of rats with silicosis. Material and Methods: Forty-eight Wistar rats were randomly divided into 3 groups. The study group (N = 16) -silicosis was induced by intratracheal instillation of 50 mg silica on day 1, and IFX was subcutaneously administered at a dose of 15 mg/kg of body weight from day 2 to day 6, the vehicle group (N = 16) -silica used as the study group but without IFX, the sham group (N = 16) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 36 publications
0
17
1
Order By: Relevance
“…TNF pro-inflammatory cytokine overexpression and involvement in silica-induced sponge collagen biosynthesis was demonstrated in quartz-treated explants as compared with controls by means of specific TNF inhibitors affecting the fibrogenic gene response [36]. Zhang et al have found that anti-TNF may improve silica-induced pulmonary inflammation by decreasing the TNF-α, inhibiting NF-κB signaling as well as oxidant status, which suggest that anti-TNF has potential role in the treatment of silica-induced lung damage [37]. On the other hand, several studies discussed association of TNF gene polymorphisms in patients with silicosis, but results were inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…TNF pro-inflammatory cytokine overexpression and involvement in silica-induced sponge collagen biosynthesis was demonstrated in quartz-treated explants as compared with controls by means of specific TNF inhibitors affecting the fibrogenic gene response [36]. Zhang et al have found that anti-TNF may improve silica-induced pulmonary inflammation by decreasing the TNF-α, inhibiting NF-κB signaling as well as oxidant status, which suggest that anti-TNF has potential role in the treatment of silica-induced lung damage [37]. On the other hand, several studies discussed association of TNF gene polymorphisms in patients with silicosis, but results were inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its inflammatory role, it stimulates the release of TGF-β1 and has an important role in glomerular inflammation and fibrosis [18]. Previous studies on different models of fibrosis showed that Infliximab (IFX), a monoclonal antibody for TNF-α [19], attenuates effectively the fibrosis and the induced inflammation via decreasing the TNF-α and inhibiting nuclear factor kappa-B, NF-κB [20,21]. However its effect on improving RF induced by IR has not been studied yet.…”
Section: Introductionmentioning
confidence: 99%
“…In silica-and bleomycin-induced mice models of pulmonary fibrosis, infusion of a human recombinant soluble TNF receptor (rsTNFR-β), which acts as a TNFα antagonist, decreased biochemical markers of lung fibrosis (contents of hydroxyproline and collagen), reduced the proportion of areas in the damaged lung and, in the silicosis model, diminished the formation of nodules with rich collagen contents [100]. Administration of infliximab, a monoclonal immunoglobin G neutralizing TNFα biological activity, to rats with silica-induced acute lung injury significantly improved lung pathological changes, decreased the count of inflammatory cells and collagen deposition, declined TNFα in serum and BALF, and suppressed NF-κB signaling and expression of inducible NOS [102]. Similarly, pretreatment with infliximab in bleomycin-instilled rats effectively prevented them from inflammation, oxidative stress, and lung fibrosis [101].…”
Section: Other Agentsmentioning
confidence: 97%